Readings in Latin American modern art - Frank, Patrick, 1953- (Yale University Press, 2004)
This important and welcome volume is the first English-language anthology of writings on Latin American modern art of the twentieth century. The book includes some fifty seminal essays and documents; including statements, interviews, and manifestoes by artists; that encompass the broad diversity of this emerging field. Many of these materials are difficult to access and some are translated here for the first time. Together the selections explore the breadth and depth of Latin American modern art as well as its distinctive evolution apart from American and European art history.Included in this collection are fascinating ideas and insights on the impact of the avant-garde in the 1920s, the Mexican mural movement, Surrealism and other fantasy-based styles, modern architecture, geometric and optical art, concrete and neo-concrete art, and political conceptualism. For students and scholars of Latin American art, the volume offers an invaluable collection of primary and secondary sources